Efficiency of Organic Corrosion Inhibitors Derived from Thai-Bael Fruit Extract for Preventing Corrosion in Carbon Steels - Manantapong, Phattarasuda; Chaipunya, Nattanon; Wannapaiboon, Suttipong; Chirawatkul, Prae; Wattanathana, Worawat; Hanlumyuang, Yuranan (Asian Journal of Chemistry, 2020)
The inhibiting action of Thai-bael fruit extract at room temperature on hot-rolled steel in 1M HCl solution was studied. The chemical functional groups of the green inhibitors were characterized by Fourier-transformed infrared spectroscopy. The electrochemical activities of steel surface were investigated through linear polarization measurements, electrochemical impedance spectroscopy, surface assessment techniques based on optical microscopy and X-ray absorption spectroscopy. Electrochemical testing samples have been prepared in the form of square plates with the size 1 × 1 cm2. The organic corrosion inhibitor extract from Thai-bael fruit has shown the smallest corrosion current density (Icorr) of 114.8 μA cm-2 and corrosion potential (Ecorr) of -424.6 mV, compared with standard Ag/AgCl electrode potential. In comparison, similar tests in the bare HCl solutions yielded Icorr = 882.4 mA cm-2 and Ecorr = -445.8 mV. The mixed-type corrosion inhibiting behaviour was evidenced in the results of the polarization measurements. Electrochemical impedance spectroscopy reveals that the resistance to charge transfer due to the presence of the extracts has been increased by about four times that of the same test on the bare HCl solution, indicating the formation of a protective layer. The adsorption of the organic molecules near the steel-electrolyte interface is evident in the decreasing double-layer capacitance with the enhancing concentration levels of the extract. This latter finding supports the displacement of the water molecules by means of the adsorption of the inhibitors on the steel surface. The optical images of steel surface before and after being immersed in HCl solution also showed pieces of evidence of corrosion retardation. XANES study as well as the linear combination fitting revealed that the samples immersed in HCl solutions with Thai-bael fruit extract possess less Fe3+ compositions. All tendencies across the four examinations indicate that Thai-bael fruit extract could potentially inhibit the corrosion reaction of steel electrodes in the acidic solution.